Control of pulsed beam parameters at the exit channel of the high-intensity linac - Vereshchaka, V.N.; Dovbnya, A.N.; Dronov, R.N.; Myakushko, L.K.; Reprintsev, L.V.; Savchenko, A.N.; Sarvilov, A.A.; Tatanov, V.I.; Shevchenko, V.A.; Shendrik, V.A.; Boriskin, V.N. (Вопросы атомной науки и техники, 2014)
Control of beam parameters is important for maintenance of linac operating conditions, as well as, for securing a high-speed protection of exit channel components against the beam damage. For this purpose the beam current, beam center position and ellipse cross-section (10 MeV, 10 kW, 1 А/pulse, 300 Hz, 3.5 μs) are measured at the output part of linac. Two similar current sensors, position sensor and water-cooled copper collimator in the gap between the current sensors were used. All the sensors of a magnetic induction type have windings on ferrite coils placed in vacuum. The system is described and the component calibration results are reported. The coefficient of beam losses during the transit through the collimator is calculated with the use of a special microprocessor placed in the ADC module which receives the signal from two current sensors. An algorithm of signal digitization eliminates the failures under the action of pulse interference. When the set threshold of beam losses is exceeded, the signal from the electron source blocking enters into the linac synchronization unit. Control of position sensor signals is carried out without beam chopping by the on-line comparison between the four position sensor signals and the current sensor signal being placed in the same case. The data on the beam parameters are displayed on the PC screen. The system is successfully used during several years. Контроль параметров пучка важен как для поддержания режима работы ЛУЭ, так и для организации быстрой защиты от поражения элементов выходного тракта пучком. Для этого на тракте вывода пучка (10 МэВ, 10 кВт, 1 А/имп., 300 Гц, 3,5 мкс) измеряются ток пучка, положение его центра и эллиптичность поперечного сечения. Использованы два идентичных датчика тока, датчик положения и водоохлаждаемый медный коллиматор в промежутке между датчиками тока. Все датчики магнитоиндукционного типа с обмотками на ферритовых кольцах, помещенных в вакуум. Описана конструкция и приведены результаты калибровки всех элементов. Коэффициент потерь пучка при пролёте коллиматора рассчитывается специальным микропроцессором, размещённым в модуле АЦП, на который поступают сигналы от двух датчиков тока. Алгоритм оцифровки сигналов устраняет сбои при воздействии импульсной помехи. При превышении установленного порога потерь пучка в блок синхронизации ЛУЭ поступает сигнал блокировки источника электронов. Контроль сигналов с датчика положения без прерывания пучка проводится путём оперативного сравнения суммы четырёх сигналов датчика положения с сигналом датчика тока, размещённых в одном корпусе. Данные о параметрах пучка выведены на дисплей ЭВМ. Система успешно используется в течение нескольких лет. Контроль параметрів пучка важливий як для підтримки режиму роботи ЛПЕ, так і для організації швидкого захисту від поразки елементів вихідного тракту пучком. Для цього на тракті виводу пучка (10 МеВ, 10 кВт, 1 А/імп., 300 Гц, 3,5 мкс) вимірюються струм пучка, положення його центра та еліптичність поперечного перерізу. Були використані два ідентичних датчика струму, датчик положення та водоохолоджуваний мідний коліматор проміж датчиками струму. Всі датчики магнітоіндукційного типу з обмотками на феритових кільцях, які знаходяться у вакуумі. Описана конструкція та приведені результати калібровки усіх елементів. Коефіцієнт витрат пучка при прольоті коліматора розраховується спеціальним мікропроцесором, який знаходиться у модулі АЦП, на який приходять сигнали від двох датчиків струму. Алгоритм оцифровки сигналів зменшує вплив імпульсної перешкоди. При перевищенні встановленого порогу втрат пучка в блок синхронізації ЛПЕ подається сигнал блокування джерела електронів. Контроль сигналів з датчика положення без переривання пучка здійснюється шляхом оперативного порівняння суми чотирьох сигналів датчика положення з сигналом датчика струму, які розміщені в одному корпусі. Параметри пучка виводяться на дисплей комп’ютера. Система успішно використовується на протязі декількох років.